Assessment Of Polychlorinated Dioxins/Furans In Ambient Air And Soil Samples From Selected Industrial Sites Using Palm Kernel Shell Activated Carbon In A Modified Sample Preparation Method - Ahmad, Abdul Rahim (2012)
For the first time an assessment of dioxins/furans in ambient air and soil samples in Malaysian environment is reported. Three (3) industrial sites and one (1) pristine site were selected for this study and samples were analysed using a modified sample preparation method. The analysis involves the quantification of seventeen congeners of dioxins/furans present in the ambient air and soil samples. The highest dioxins/furans concentrations in ambient air were found in Taiping area ranging from 0.056 to 0.167 i-TEQ pg/Nm3. This was followed by Bukit Pelanduk area with dioxins/furans concentrations ranging from 0.080 I-TEQ to 0.113 i-TEQ pg/Nm3. The third site, which is in the Prai area recorded the lowest dioxins/furans concentrations, ranging from 0.029 to 0.099 i-TEQ pg/Nm3, while the pristine site in Kuala Tahan National Park area recorded the dioxins/furans concentration in the range of 0.003 to 0.006 i-TEQ pg/Nm3. The most abundant congeners in all air samples in these areas were 2,3,4,7,8 – PeCDF and 1,2,3,7,8 – PeCDD. This study also allows the prediction of dioxins/furans emission rate of different incinerator stacks by data fitting of the observed ambient air dioxins/furans concentration in the Gaussian air dispersion model. Other interesting finding in this study was that during periods of haze, it is evident that there is a correlation between the particulate matter concentrations (indicated by Air Pollution Index) and dioxins/furans concentrations in air. Wind speed and prevailing wind directions were found to contribute to the distributions of dioxins/furans emitted from incinerators to different distances.